2004
DOI: 10.1161/01.cir.0000148686.95696.1e
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Blood Flow Assessment After Successful Angioplasty for Acute Myocardial Infarction Predicts the Risk of Long-Term Cardiac Events

Abstract: Background-Analysis of coronary flow velocity (CFV) in the recanalized infarct-related coronary artery (IRA) with a Doppler guidewire is useful for predicting recovery of regional left ventricular function, in-hospital complications, and survival. We postulated that the CFV pattern after IRA reperfusion for acute myocardial infarction (AMI) would predict long-term adverse cardiac events. Methods and Results-Sixty-eight consecutive patients with a first AMI underwent CFV measurement with a Doppler guidewire aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 33 publications
(27 reference statements)
1
22
0
1
Order By: Relevance
“…vascular damage, predicted the risk of long-term cardiac events after acute myocardial infarction 19 .…”
Section: I-53mentioning
confidence: 99%
“…vascular damage, predicted the risk of long-term cardiac events after acute myocardial infarction 19 .…”
Section: I-53mentioning
confidence: 99%
“…However, successful restoration of epicardial flow does not necessarily translate into optimal reperfusion at the myocardial tissue level, and may result in microvascular See page 2239 obstruction (MO), also known as the "no-reflow" phenomenon (2). Experimental and clinical studies have demonstrated that MO is a common phenomenon and is associated with increased infarct size, reduced myocardial function, left ventricular (LV) remodeling, and worse clinical outcome (3)(4)(5)(6)(7)(8)(9)(10)(11). As a consequence, MO has important prognostic significance in patients after acute MI.…”
mentioning
confidence: 99%
“…The small sample size may also explain why the diastolic deceleration time and the presence of systolic flow reversal in the infarctrelated artery did not predict mortality, whereas they have in other studies. 11,12 What remains unclear from this study is why some patients had a low CFVR in the nonculprit vessel and why this was predictive of adverse outcomes. Perhaps, the most likely explanation is that CFVR in the nonculprit vessel may be a reflection of the effects of a larger infarction on the wall motion in remote territories, the left ventricular end-diastolic pressure, and the neurohumoral response, all of which have been implicated in changes in coronary flow.…”
Section: Circ Cardiovasc Intervmentioning
confidence: 88%